Primary High-Grade Neuroendocrine Carcinoma of the Heart - Guajardo-Salinas, Gustavo E. (Texas Heart Institute, 2013)
We report the successful resection of a solitary, apparently primary, high-grade neuroendocrine carcinoma of the heart, in a 70-year-old man who had presented with progressive dyspnea. The tumor occupied the right atrium and almost completely obstructed the superior and inferior venae cavae; it also involved the aortic root and the interatrial septum. To postpone the patient's impending cardiac failure, we resected the gross tumor except in the region of the aortic root and the trigone, which we debulked. We completely reconstructed the right atrium with pericardium and the interatrial septum with a pericardial patch. The patient recovered uneventfully; 18 months postoperatively, he had experienced only local recurrence in the tumor bed. This case shows that the palliative resection of large neuroendocrine tumors of the heart can yield good outcomes and prolong patient survival. To our knowledge, ours is the only report of a high-grade neuroendocrine cardiac tumor of apparently primary origin to have been resected with good palliative results.